Biotechnology and development : challenges and opportunities for Asia - International Conference on Biotechnology and Development: Challenges and Opportunities for Asian Region (2002 : New Delhi, India); Chaturvedi, Sachin; Rao, S. R., Dr.; Research and Information System for the Non-aligned and Other Developing Countries (New Delhi : Academic Foundation, 2004)
Contributed articles presented earlier at the International Conference on Biotechnology and Development: Challenges and Opportunities for Asian Region, February 26-27, 2002 at New Delhi, India organized by RIS.
"Research in Information System for the Non-Aligned and Developing Countries, New Delhi."
Includes bibliographical references.
oif 15/09/15
Loan
Keywords: Biotechnology -- Asia -- Congresses; Biotechnology industries -- Asia -- Congresses; Asia -- Economic conditions -- 1945- -- Congresses